Avaliação dos efeitos induzidos pela 5-hidroxiflavona sobre o sistema cardiovascular de ratos - Lins, Larissa Suelen da Silva (2022)
Flavonoids are bioactive polyphenols known to present, for the most part, cardioprotective action, being effective in the treatment of cardiovascular diseases such as arterial hypertension. In this work, some effects induced by the flavonoids flavone (FVN), 3-hydroxyflavone (3FVN) and 5-hydroxyflavone (5FVN) were verified in normotensive rats, using in silico, ex vivo, and in vivo approaches. In ex vivo experiments, we evaluated the relaxing effect promoted by FVN, 3FVN or 5FVN in the isolated superior mesenteric artery of rats pre- contracted with phenylephrine (Phen 10 μM). In order to investigate the mechanism of action of 5FVN, other experimental protocols were used, such as pre-contraction of the rings with 60 mM and 20 mM KCl depolarizing solutions, and the incubation of the rings in the presence of ion channel blockers, glibenclamide (1mM) and 4-aminopyridine (10 μM). Then, through in vivo experiments, it was possible to analyze the physiological effect induced by the acute intravenous administration of different doses of 5FVN on blood pressure and heart rate of non-anesthetized rats. The in silico results demonstrated a series of potential beneficial cardiovascular activities associated with the compounds, such as vasodilator, antioxidant and cardioprotective action. The ex vivo protocols demonstrated that the compounds FVN, 3FVN and 5FVN showed concentration-dependent vasorelaxant activity in rings pre-contracted with FEN. Removal of the endothelium did not alter the effect induced by the compounds. When comparing pD2 values, it was observed that 5FVN was the most potent in promoting vasorelaxation, when compared to 3FVN and FVN, both in rings with intact endothelium and in rings whose endothelium was removed. Therefore, 5FVN was chosen for future analyses. The vasodilatory effect of 5FVN was attenuated when vascular rings were pre-contracted with 60 mM KCl compared to pre-contracted with PHE in the absence of functional endothelium. The incubation of the rings with KCl 20 and glibenclamide was not able to change the 5FVN concentration response curve compared to the control group, since in the presence of 4-aminopyridine there was a significant attenuation in the 5FVN response and, therefore, we suggest that the effect of Compound occurs through Kv channels. Acute intravenous administration of doses 1mg/kg; 5mg/kg; 10mg/kg and 20mg/kg of 5FVN caused hypotension and tachycardia in non- anesthetized normotensive rats. It is concluded that, among the flavonoids analyzed, 5FVN has the greatest potency in exerting vasorelaxation in superior mesenteric artery rings of normotensive rats. The relaxation induced by this compound is independent of the functional endothelium and involves voltage- gated K+ channels (Kv) present in vascular smooth muscle. 5FVN-induced vasodilation likely contributes to the hypotension observed in non-anesthetized normotensive rats.